Ischemic strokes in COVID-19: risk factors, obesity paradox, and distinction between trigger and causal association - Janes, Francesco; Sozio, Emanuela; Gigli, Gian Luigi; Ripoli, Andrea; Sbrana, Francesco; Kuris, Fedra; Nesi, Lorenzo; Semenzin, Tosca; Bertolino, Giacomo; Deana, Cristian; Bagatto, Daniele; Ciardi, Chiara; et al. (Frontiers in Neurology, 2023)
Background and Purpose. Stroke has been described as a Covid-19 complication. However, its occurrence rate, risk factors and causal relationship are still not well established.We describe the characteristics of confirmed Covid-19 related strokes among all cases of Covid-19 hospitalized in our Health System, from November 01 st 2020 to April 30 th , 2021. Risk factor analysis has been conducted for ischemic stroke (IS), which represents 92% of all confirmed strokes, and a "causal attribution to infection" classification is provided.Results. 62/4105 hospitalized Covid-19 patients had an acute stroke (1.51%). Severe Covid-19 (OR 2.27 -CI 1.06 -4.77; p = 0.032), atrial fibrillation (OR 3.65 -CI 1.63 -7.98; p = 0.001), and ischemic heart disease (OR 4.590 -CI 1.714 -12.137; p = 0.002) proved independent risk factors for IS, while obesity was a protective factor (OR 0.90 -CI 0.82 -0.97; p = 0.012).Covid-19 had a causal role in 32.1% of IS, was a relevant cofactor in 28.6%, and a possible trigger in 39.3% of events.Our stroke occurrence rate is consistent with other population-based reports (range 0.34 -2.7%). Prespecified peculiar clinical and radiological features allow the distinction between "IS caused by Covid-19" and "IS triggered by Covid-19". Clinical History of vascular diseases and risk factors is crucial in determining the risk of IS in these patients. However, the protective effect of a BMI > 30 kg/m 2 seems to suggest an obesity paradox.Stroke is a complication of Covid-19 in 1.51% of hospitalized patients. • In Covid-19 patients 32.1% of strokes are likely to be caused by infection induced coagulopathy, while 67.9% are probably or possibly triggered by viral infection. • Covid severity, Atrial Fibrillation and Ischemic Heart Disease are independent risk factors for Acute Stroke in Covid-19 patients. • Higher BMI and Obesity paradoxically proved to protect from ischemic stroke occurrence in Covid-19 patients. • The independent association of the most severe Covid-19 forms with stroke occurrence encourages the need for effective and long-lasting vaccination against Covid-19.